Prices as Aggregators of Private Information: Evidence from S&P 500 Futures Data - Cho, Jin-Wan; Krishnan, Murugappa (Journal of Financial and Quantitative Analysis, 2000)
Jin-Wan Cho, Murugappa Krishnan, Prices as Aggregators of Private Information: Evidence from S&P 500 Futures Data, The Journal of Financial and Quantitative Analysis, Vol. 35, No. 1 (Mar., 2000), pp. 111-126